Capacity building in pharmacy education in resource-poor settings: an ethnographic case study of Malawi - Lim, Zon Be (2013)
In many low-income countries, the disease burden is high but health workers are scarce. To increase the number of health workers, one of the most urgent tasks is to produce more health workers. Grounded in the disciplinary focus of pharmacy, this research looks for alternative, innovative strategies to build the capacity of an education institution in a resource-poor setting. Malawi was chosen as a case study country because of its newly established pharmacy degree programme. A broadly ethnographic approach is employed in order to enhance cultural sensitivity and to understand capacity problems from an insider perspective. The fieldwork took place in 2010 and explored a wide range of pharmaceutical activities in the country. An interpretivist epistemology has also facilitated this research to cross beyond its science-based roots in the ‘human resource for health’ (HRH) research paradigm into other disciplinary areas, notably education and African Studies. The first objective of this study was to explore the roles of pharmacists in Malawi. It was agreed by all stakeholders that pharmacists should become managers of medicines, particularly at the district hospitals. Pharmacists were expected to solve the chronic problems of rampant drug pilferage and shortages in essential drugs. Although pharmacy technicians had traditionally assumed the managerial roles at district hospitals, they were deemed unfit for these roles at present day. Some were even accused of stealing drugs. This phenomenon was caused by multiple contextual factors, including a new perception about professionalism. Because of their professional titles, pharmacists were perceived to be superior to the pharmacy technicians in terms of knowledge, power and ethics. This perception was not supported by concrete evidence of pharmacists’ more superior behaviour. A deeper investigation revealed this perception was most probably shaped by colonial legacies and Western views. Home grown definition of professionalism was suppressed because it was not an agenda deemed important by the community of global health governance. The primary agenda by the global health governance to scale up service delivery, but ignoring the growth of domestic agendas for professionalism, may need reconsidering in post-Millennium Development Goal era.